Green Introspection. - Cameron, Kirk W. (Computer (00189162), 2009)
This article discusses the role of computers in the consumption of energy that contributes to the global load of pollution. Estimates regarding the level of energy consumption by server farms and data centers in the U.S. are analysed in terms of their contribution to global warming. Issues relating to the environmental impact of computer parts and peripherals are also noted. The development of Energy Star regulations for servers developed in the U.S. is discussed. Research by the television program "60 Minutes" into pollution resulting from the disposal of electronic products is also addressed.